Low Tenacity of Toxoplasma gondii Tachyzoites In Vitro - Thomas Grochow; Mirjam Kalusa; Pauline Tonndorf-Martini; Nicole Röhrmann; Simone A. Fietz; Lea-Christina Murnik (Microorganisms)
Toxoplasma gondii, an obligate intracellular protozoan, poses significant risks to public health due to its widespread distribution and potential for severe congenital and neurological complications. The fast-replicating tachyzoite stage is crucial for acute infection and laboratory studies, yet effective inactivation methods remain inadequately explored. This study evaluates various chemical and physical approaches to inactivate T. gondii tachyzoites in vitro. Using a combination of GFP fluorescence and viability assays, we demonstrated the complete inactivation of tachyzoites with ethanol (≥30%), hydrogen peroxide (≥3%), o-hydroxydiphenyl fatty acid eutectic with peracetic acid (≥1%), and heat treatment at 60 °C for 30 min. Our findings highlight the importance of concentration, solvent choice, and exposure time in disinfection efficacy, providing a framework for improving laboratory safety protocols. These results contribute to the refinement of inactivation strategies, supporting safer handling and research on T. gondii in vitro while reducing reliance on animal models.